2008
DOI: 10.1002/iroh.200610935
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Detection and Quantification of Polyphosphate and Polyphosphate Accumulating Microorganisms in Aquatic Sediments

Abstract: It has been speculated that the microbial P pool is highly variable in the uppermost layer of various aquatic sediments, especially when an excessive P accumulation in form of polyphosphate (Poly-P) occurs. Poly-P storage is a universal feature of many different organisms and has been technically optimised in wastewater treatment plants (WWTP) with enhanced biological phosphorus removal (EBPR). In the recent past, new insights into mechanisms of P elimination in WWTP almost exclusively depended on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 145 publications
(205 reference statements)
1
52
0
Order By: Relevance
“…Phosphorus-31 nuclear magnetic resonance spectroscopy requires large sample sizes and may be insensitive to polyP tightly associated with metal cations in solid granules. Moreover, alkaline extractions may incompletely extract and partly hydrolyze polyP (30,31). Assays based on enzymes of polyP metabolism (either exopolyphosphatase followed by orthophosphate [PO 4 3Ϫ ] determination [32,33] or polyP kinase followed by ATP measurement [34,35]) entail purifying polyP, but purification procedures suffer from low yields (36,37) and there is no commercial source for the necessary enzymes.…”
mentioning
confidence: 99%
“…Phosphorus-31 nuclear magnetic resonance spectroscopy requires large sample sizes and may be insensitive to polyP tightly associated with metal cations in solid granules. Moreover, alkaline extractions may incompletely extract and partly hydrolyze polyP (30,31). Assays based on enzymes of polyP metabolism (either exopolyphosphatase followed by orthophosphate [PO 4 3Ϫ ] determination [32,33] or polyP kinase followed by ATP measurement [34,35]) entail purifying polyP, but purification procedures suffer from low yields (36,37) and there is no commercial source for the necessary enzymes.…”
mentioning
confidence: 99%
“…It is more effective than other staining procedures, because it produces higher contrast between the cell and the granules (Serafim et al, 2002). However, because of the detection limits of the optical microscopy, and knowing that none of the available dyes are exclusively specific for poly-P, staining results must be judged with caution and Neisser positive bacteria have to be indicated as potential PAO until storage material can be chemically characterized as poly-P (Kulaev & Kulakovskaya, 2000;Hupfer et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…When P levels were adequate in the water, a substantial portion of P was stored in microbial cells in the form of nucleic acids, phospholipids, sugar phosphate, and other organic P compounds (Haglund et al 2003;Uhlmann et al 1998). Some of these compounds may be assimilated by the decomposers and some may be released as inorganic P. It has been suggested that some of the fixed P may eventually become particulate refractory organic P compounds and was buried in the sediments (Gächter and Meyer 1993;Hupfer et al 2008). The microbial P adsorption is a process during which microorganisms assimilate P for development.…”
Section: Discussionmentioning
confidence: 98%